PENYETARAAN JABATAN ADMINISTRASI KE DALAM JABATAN FUNGSIONAL DALAM PERSPEKTIF UNDANG-UNDANG NOMOR 5 TAHUN 2014 TENTANG APARATUR SIPIL NEGARA - Prianto Prianto (JURNAL AKTA YUDISIA, 2022)
AbstractThe Ministry of State Apparatus Empowerment and Bureaucratic Reform simplified the bureaucracy by trimming the positions of echelon III and Echelon IV by issuing Minister of State Apparatus Empowerment and Bureaucratic Reform Regulation Number 17 of 2021 concerning Equalization of Administrative Positions into Functional Positions. This equalization of positions aims to create a more dynamic and professional bureaucracy as an effort to increase effectiveness and efficiency to support the performance of government services to the public. In principle, the goal of equalization is for a system of career development and employee welfare.Based on the background, the issues raised in this research are, first, the Equalization of Position Arrangements in the PANRB Regulation Number 17 of 2021 concerning the Equalization of Administrative Positions into Functional Positions, and the second problem is the Career Pattern of Functional Positions as a result of Equality in the Perspective of Law Number 5 of 2014 concerning the State Civil Apparatus. In this research, the type of normative legal research is used, with the approach used is the Statute approach and the conceptual approach.The results of the research show that legally, Permenpan RB Number 17 of 2021 is contrary to Law Number 5 of 2014 concerning ASN and Government Regulation Number 11 of 2017 concerning PNS Management. The mechanism for removing administrative positions through the Permenpan RB is normatively contrary to the Elucidation Chapter of Article 7 paragraph (2) of Law no. 12 of 2011 concerning the Establishment of Legislation which states that every principle that lower laws may not conflict with higher laws. The equalization of administrative to functional positions as a solution actually presents an ineffective and efficient bureaucracy which will certainly greatly impact ASN's future career pattern. Keywords: Regulation, Equalization, Career Patterns, Functional Positions, Administrative Positions